Russia's new nuclear doctrine. Russian policy of deterrence. - slawomir.kleszcz@wat.edu.pl Sławomir J. (2022)
The main purpose of the article is to address the issues arising from the new nuclear doctrine of Russia. An attempt to analyze the document is "Russia's Nuclear Doctrine" as a new tool for the Russian Federation's nuclear deterrent policy. The performance changes over the years in Russia's approach to the use of nuclear weapons in the new doctrine in the times of the Soviet Union in global terms, as well as in the micro-region of Central Europe, especially during the war in Ukraine.